Standardization of a cytometric p24-capture bead-assay for the detection of main HIV-1 subtypes - Merbah, Mélanie (J Virol Methods, 2016)
The prevailing method to assess HIV-1 replication and infectivity is to measure the production of p24 Gag protein by enzyme-linked immunosorbent assay (ELISA). Since fluorescent bead-based technologies offer a broader dynamic range and higher sensitivity, this study describes a p24 capture Luminex assay capable of detecting HIV-1 subtypes A, B, C, D, circulating recombinant forms (CRF) CRF01_AE and CRF02_AG, which together are responsible for over 90% of HIV-1 infections worldwide. The success of the assay lies in the identification and selection of a cross-reactive capture antibody (clone 183-H12-5C). Fifty-six isolates that belonged to six HIV-1 subtypes and CRFs were successfully detected with p-values below 0.021; limits of detection ranging from 3.7 to 3×10(4) pg/ml. The intra- and inter-assay variation gave coefficient of variations below 6 and 14%, respectively. The 183-bead Luminex assay also displayed higher sensitivity of 91% and 98% compared to commercial p24 ELISA and a previously described Luminex assay. The p24 concentrations measured by the 183-bead Luminex assay showed a significant correlation (R = 0.92, p<0.0001) with the data obtained from quantitative real time PCR. This newly developed p24 assay leverages the advantages of the Luminex platform, which include smaller sample volume and simultaneous detection of up to 500 analytes in a single sample, and delivers a valuable tool for the field.